2010
DOI: 10.1371/journal.pbio.1000368
|View full text |Cite
|
Sign up to set email alerts
|

Segment-Specific Neuronal Subtype Specification by the Integration of Anteroposterior and Temporal Cues

Abstract: To address the question of how neuronal diversity is achieved throughout the CNS, this study provides evidence of modulation of neural progenitor cell “output” along the body axis by integration of local anteroposterior and temporal cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
135
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(150 citation statements)
references
References 103 publications
13
135
0
Order By: Relevance
“…Although such a mechanism may account for varying Antp levels in LinA, it is also possible that Antp is continuously expressed in the LinA NB, but not in its progeny, resulting in its gradual decline in post-mitotic neurons. Leveldependent functions have also been observed for the Hox accessory protein FoxP1 in vertebrate MNs and for Hth in Drosophila embryonic lineages (Dasen et al, 2008;Karlsson et al, 2010). However, these two cases are distinct from the Chinmo and Antp examples, which influence cell fates within individual NB lineages.…”
Section: Research Articlementioning
confidence: 94%
See 1 more Smart Citation
“…Although such a mechanism may account for varying Antp levels in LinA, it is also possible that Antp is continuously expressed in the LinA NB, but not in its progeny, resulting in its gradual decline in post-mitotic neurons. Leveldependent functions have also been observed for the Hox accessory protein FoxP1 in vertebrate MNs and for Hth in Drosophila embryonic lineages (Dasen et al, 2008;Karlsson et al, 2010). However, these two cases are distinct from the Chinmo and Antp examples, which influence cell fates within individual NB lineages.…”
Section: Research Articlementioning
confidence: 94%
“…For example, in the abdomen the Hox gene abdominal A (abd-A) induces NB apoptosis in a subset of lineages that continue to produce progeny in thoracic segments (Bello et al, 2003;Cenci and Gould, 2005;Maurange et al, 2008). Abdominal Hox genes also have the ability to induce NB cell cycle exit in some abdominal lineages (Karlsson et al, 2010). Finally, the Hox gene Abdominal-B (Abd-B) can block or promote apoptosis of neurons, depending on the context (MiguelAliaga and Thor, 2004;Suska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The temporality of development is pivotal in the cell fate specification and neural diversity. Studies in Drosophila have identified a hierarchy of transcription factors, expressed sequentially in NBs which, with other factors such as Hox genes, determine their temporal identities and the fate of their progeny [123]. These factors include; Hunchback (Hb), Kruppel (Kr), Pdm (Nubbin/Pdm1 and Pdm2), Castor (Cas) and Grainy head (Grh) [124].…”
Section: Temporal Progression Of Neuro-developmentmentioning
confidence: 99%
“…2) Cell cycle exit followed by programmed cell death (PCD) e.g., NB5-6T. 3) PCD e.g., NB7-3 [122,123,127,129,130] (Fig. 17).…”
Section: Temporal Progression Of Neuro-developmentmentioning
confidence: 99%
“…Moreover, the expression pattern of the early factors mirrors the expression of two other temporal factors present at the two last windows of the cascade i.e., cas and grh plus the Hox gene Antp. [71,296]. Due to the expression time of Cas, Grh and Antp we call these tree genes late factors from now on.…”
Section: Early Factors and Late Factors Interplay Govern Nb Identitymentioning
confidence: 99%